Psycho-social factors influencing maladjustive behaviour among delinquent pupils in selected secondary schools in Ibadan (2007)
The study examined the psycho-social factors influencing maladjustive behaviour among pupils in some secondary schools in Ibadan. A total of 180 senior secondary school pupils drawn from five secondary schools in Ibadan were used for the study. Questionnaires and archival records were used to obtain information the forces within and outside the individual that cause maladaptive behaviour. This was done with a view to suggesting therapeutic strategies which will help in reducing the rate of delinquents in the schools. Frequency, percentage and chi-square statistical methods were used to analyse the data. Four research questions were generated and tested for the study. The findings among others showed that there was significant relationship between psycho-social factors and maladjustive behaviour (X' = 15.62, df = 6, P<0.05). Recommendations made include organizing programmes targeted at families and specifically focusing on adolescents/school children on the need to be resilient in the face of risk and adversity. The findings showed that offences like stealing) truancy, drug abuse and thuggery and many others have been used to categorise pupils being maladjusted. Findings further indicate that pupils who commit the aforementioned offences have been influenced by either problems within them or in their immediate environment like family or school.